Conhecimento etnoornitológico na zona rural do Município de Iporá, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
Ethnoornitology has the goal of understanding the cognitive, behavioral and symbolic relationships between humans and birds. Despite the importance of these animals to humans, ethnoornitological studies are still rare in Brazil. The main goal of this study is to evaluate the local knowledge on birds by rural residents in Iporá, Brazil, in four communities: Bugre, Cruzeirinho, Pé-de-Pato, and Taquari. The data were obtained through interviews in structured forms and free lists, and the systematic collection was performed between June and August 2014. 37 subjects were interviewed, eight in each community, except for Bugre (n=13). 125 ethnospecies of birds from 23 orders and 42 families were recorded. 204 vernacular names assigned to the birds were recorded. The formation of these names used behavioral criteria (feeding, mating, singing), type of habitat, anthropogenic aspects, and, especially, morphological criteria. The morphologic criteria (such as color and size of species) were the most important criteria in the identification of birds, followed by behavioral criteria (singing, diet) and habitat. The classification of birds involved morphological criteria, type of habitat, and behavior. A large ethnoecological knowledge were recorded, showed by the description of primary habitats and modified habitats explored by birds; a representation of the different dietary habits of birds and detailed description of the reproductive period and of aspects of nesting. 19 endangered species were mentioned, especially the Tinamidae family, with six ethnospecies. Impacts caused by human action (hunting, use of pesticides on crops, deforestation, expansion of plantations and fires) were considered the main problems affecting the avifauna. The practice of hunting was not very noticeable among the interviewees. They mentioned six ethnospecies currently hunted and 19 that were hunting target in the past. The domestication of wild birds is seldom practiced by the interviewees, with Amazona sp. being the only one. Benefits to humans attributed to birds were related mainly to the performance of ecosystem services. The main losses attributed to birds were economic ones, such as damage to crops, predation on domestic livestock and disease transmission. This study demonstrated that the interviewees have a great knowledge on the richness of birds, as well as on ecological aspects of these animals, are aware of environmental problems that can affect the birds, and also recognize the ecological importance of birds for the functioning of ecosystems. The interviewees also related unharmful measures to avoid damage caused by the avifauna, showing to be aware of the risks that may affect and harm these animals. We hope that the data obtained in this study will contribute to a better knowledge of the bird fauna and development of extension activities with the rural population of Iporá.
Keywords: Conhecimento etnoecológico; Etnobiologia; Ornitologia; Ethnoecological knowledge; Ethnobiology; Ornithology; CIENCIAS BIOLOGICAS